y = x² + x complete the square to obtain

y = (x + 1/2)² - 1/4

x = (y + 1/2)² - 1/4

x + 1/4 = (y + 1/2)²

±(x + 1/4)½ = y + 1/2 since x≥-1/2 y must be positive

(x + 1/4)½ = y + 1/2

(x + 1/4)½ - 1/2 = y

there ya go!!! take care buddy!!!

]]>f(x) = 2x + 1

y = 2x + 1

switch x and y

x = 2y + 1

x - 1 = 2y

x - 1 / 2 = y

so the f-1(x) = x - 1 / 2

But for some reason I can't figure out how to do that with the problem that I have now.

]]>f(x) = x^2 + x when x >= -1/2

I know the basic way to find the inverse of a function, but for some reason I can't seem to figure out what I'm doing wrong with this problem. Here's were I was going with it:

f(x) is the same as y.

y = x^2 + x

switch x and y

x = y^2 + y

here's where I get stuck - I'm trying to solve for y, so do I move the y over or something else???

Thanks for you help.

]]>